Expression and correlation analysis of Skp2 and CBX7 in cervical cancer. Issue 12 (19th July 2021) - Maimaitirexiati, Gulikezi; Tian, Ping; Maimaiti, Hatimihan; Ding, Lu; Ma, Cailing; Li, Yuting; Wang, Jing; Yan, Qi; Li, Rong
Abstract : Aims: S-phase kinase-associated protein 2 (Skp2) oncoprotein is overexpressed in a variety of cancer tissues and promotes the malignant development of cancer. The expression levels of chromobox homolog 7 (CBX7) protein are varied among different types of cancer tissues, but its role in cervical cancer is not clear. We aimed to examine the expression and clinical significance of Skp2 and CBX7 proteins as well as their correlations in cervical cancer. Methods: Immunohistochemistry was used to detect the expression of Skp2 and CBX7 proteins in the cancerous tissues and adjacent tissues of 64 patients with cervical cancer. Relevant clinicopathological data of these patients were collected, compared and analysed for the correlations. Results: The expression of Skp2 protein in cervical cancer (87.5%) was higher than that in paracancerous tissues (14.1%), and the expression was positively correlated with clinical stage, malignant degree, lymphatic metastasis, vascular invasion and interstitial invasion. The expression of CBX7 protein in cervical cancer (48.4%) was lower than that in paracancerous tissues (96.8%), and the expression was negatively correlated with clinical stage, malignant degree, interstitial invasion, vascular invasion and lymphatic metastasis. The expression of Skp2 protein and CBX7 protein in cervical cancer tissues and adjacent tissues was negatively correlated. The expression of Skp2 and CBX7 proteins was closely related to the clinicopathological features of cervical cancer. Conclusions: CBX7 may play the role of a tumour suppressor gene in cervical cancer and provide reference value for the diagnosis and new targeted treatment of cervical cancer.